Voriconazole – are we doing what we think we are? A review of voriconazole use and monitoring in respiratory patients in a London hospital. Issue 2 (28th February 2020) - Chia, Germaine; Davies, Frances; Coleman, Meg
Abstract : Background: Voriconazole is increasingly used in treatment and prophylaxis of respiratory fungal infections, but therapy carries a risk of significant side effects. Outpatient therapy has additional challenges for ensuring pre-treatment counselling of patients and fulfilling therapeutic drug monitoring (TDM) requirements. A review of local practice was performed. Methods Electronic patient records for adult Respiratory outpatients on voriconazole from November 2005 to January 2019 were retrospectively reviewed. Data was collected on patient demographics, pre-treatment counselling and TDM. Based on the results, targeted interventions were proposed. Results: 21 patients commenced voriconazole between 2005 and 2019, majority (n=10/21, 47.2%) for chronic pulmonary aspergillosis. Of the 21 patients, counselling was variable regarding the risks of hepatotoxicity (12, 57.1%) and phototoxicity (13, 61.9%), signs indicating hepatotoxicity (6, 28.6%) and phototoxicity (11, 52.4%), and taking photo-protective precautions (13, 61.9%). 60% (n=12/20) of patients had liver function tests measured weekly in their first month of commencing treatment, while phototoxicity was reviewed in only 10% (n=2/20) of patients at follow-up appointments. In 57.1% of patients (n=12/21), none of the 3 checklists available (HCP checklist and 2 local proformas) were used when commencing treatment. Conclusion: Our findings revealed a lack of consistency in information given to patients, documentation by clinicians, and in TDM, in spite of the existing checklists available. We propose an individual written management plan to empower patients to manage their treatment and guide clinicians in pre-treatment counselling and subsequent follow up of patients. A re-audit is planned for 6 months to assess the efficacy of this intervention.